Investigating the Middle Rectal Artery and its Clinical Significance - Preeti Dnyandeo Sonje; Neelesh Kanaskar; Puranam Vatsalaswamy (Negah Institute for Scientific Communication, 2020)
Introduction: The middle rectal artery is a vital artery supplying the rectum, along with the superior and inferior rectal arteries. We explored the middle rectal artery due to its importance in rectal carcinoma surgeries.  Methods: In total, 40 pelvises were obtained from the Department of Anatomy of Dr. D. Y. Patil Medical College in Pune City, India. Results: Variations were found in the origin of the middle rectal artery, including arising from the internal pudendal artery in 9 cases. In 2 cases, it was arising from the common stem of internal pudendal and inferior gluteal arteries. Arising from the inferior vesical artery was observed in 1 case; while in 2 cases, middle rectal artery was arising from the obturator artery. This is the artery that penetrates the fascia of rectum, which is essential in mesorectal excision in rectal carcinoma cases. It forms anastomosis with superior rectal artery. Conclusion: In the low anterior resection of the rectum, the middle rectal artery is always exposed.